2018
DOI: 10.1016/j.ecoenv.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Osteotoxicity of 3-methylcholanthrene in fish

Abstract: Many chemicals produced by human activities end up in the aquatic ecosystem causing adverse developmental and reproductive effects in aquatic organisms. There is evidence that some anthropogenic chemicals disturb bone formation and skeletal development but the lack of suitable in vitro and in vivo systems for testing has hindered the identification of underlying mechanisms of osteotoxicity. Several fish systems - an in vitro cell system to study extracellular matrix mineralization and in vivo systems to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Data presented in this article-i.e., the reduced growth of the opercular bone, the increased incidence of skeletal deformities, the impaired stiffness of regenerated bone, and the differential expression of bone marker genes-provide clear evidence of an anti-osteogenic or osteotoxic effect of cadmium at doses that can be found in the aquatic environment [31,32]. A decreased operculum growth rate was recently evidenced in zebrafish larvae exposed to cobalt chloride [33] and 3-methylcholanthrene [30] through mechanisms still poorly understood but possibly related to an impairment of osteoblast (bone forming cells) maturation and function. In this regard, cadmium was found to inhibit extracellular matrix mineralization in osteoblast MC3T3-E1 cell cultures [34] but also to decrease the expression marker genes central to osteoblast maturation and function (this study).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Data presented in this article-i.e., the reduced growth of the opercular bone, the increased incidence of skeletal deformities, the impaired stiffness of regenerated bone, and the differential expression of bone marker genes-provide clear evidence of an anti-osteogenic or osteotoxic effect of cadmium at doses that can be found in the aquatic environment [31,32]. A decreased operculum growth rate was recently evidenced in zebrafish larvae exposed to cobalt chloride [33] and 3-methylcholanthrene [30] through mechanisms still poorly understood but possibly related to an impairment of osteoblast (bone forming cells) maturation and function. In this regard, cadmium was found to inhibit extracellular matrix mineralization in osteoblast MC3T3-E1 cell cultures [34] but also to decrease the expression marker genes central to osteoblast maturation and function (this study).…”
Section: Discussionmentioning
confidence: 97%
“…To get insights into the molecular mechanisms underlying cadmium anti-osteogenic effects, a CIGNAL cell-based reporter assay was used to monitor the activity of 45 signaling pathways involved in processes central to cell biology (see manufacturer website for details). Since cellular hosts of fish origin were found not to be suitable for this analysis (mineralogenic fish cells are hard-to-transfect cellular hosts [30]) and because pathway responsive elements are designed according to mammalian sequences, mouse ATDC5 (chondroprogenitor cells), and MC3T3-E1 (osteoblast precursor cells) lines were used to host the reporter constructs. While the activity of various signaling pathways was detected in both cell lines (21 pathways activated in MC3T3-E1 and ATDC5; see Figure S1 in Supplementary Materials), only 6 pathways showed an activity higher than a 2-fold change over the control.…”
Section: Molecular Pathways and Genes Targeted By Cadmiummentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, gilthead seabream VSa13 cell line ( [32]; Cellosaurus accession no. CVCL_S952) was successfully used in small-scale screening of mineralogenic extracts from marine green algae [33], halophytes [34], cyanobacteria (J. Rosa unpublished data), or environmental osteotoxic pollutants [35,36]. Typically, compounds are dissolved in culture medium and exposed to the mineralizing cells in multiwell plates (Figure 1A).…”
Section: In Vitro Cell Systems Capable Of Biomineralizationmentioning
confidence: 99%
“…For the male reproductive system, dioxin reduces the number and maturity of sperm cells, causing maternalism, which significantly affects reproduction in animals [ 19 ]. Studies have shown that exposure to 3-MC causes damage to cells, tissue, and organs [ 20 , 21 , 22 , 23 , 24 ]. Numerous studies have shown that 3-MC exposure rechanges cell adhesion and induces cell apoptosis [ 25 , 26 , 27 ], affecting the immunity and metabolism of tissue, which in turn leads to the retention of carcinogenic substances in tissues and makes organs cancerous [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%